Simple method for obtaining regenerated cellulose nanoparticles from delignifed cofee parchment, and their use in fabricating blended flms (2023)
ABSTRACT: Cofee parchment is one of the residues generated in cofee processing and has been poorly explored for value-added applications. It has been reported that cofee parchment has a high cellulose content (40–49%). Cellulose has been studied in many felds and specifcally regenerated cellulose has been explored for many applications. Then, in this work a simple method for obtaining regenerated cellulose nanoparticles (RCNPs) from delignifed coffee parchment, was determined. A complete physico- chemical characterization of RCNPs obtained is presented, FTIR showed high cellulose purity, and XRD analysis showed high crystallinity of cellulose II. TEM images revealed that nanoparticles have spheri- cal morphology. TGA showed good thermal stability and DLS allowed to determine the stability of suspension and the Z-average of the particles. The application of RCNPs on flm formation was also evaluated when blended with PVA and Glycerol showing good mechanical properties with potential application on food packing.